Does Corporate Social Responsibility Reduce Earnings Management? The Moderating Role of Corporate Governance and Ownership - Ajina, Aymen; Lakhal, Faten; Ayed, Sabrine (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
The purpose of this paper is to investigate the relationship between corporate social responsibility and earnings management and the moderating effect of corporate governance and ownership structure on this relationship. Using panel data for a sample of French listed companies between 2010 and 2013, we find that CSR engagementconstrain earnings management practices suggesting that managers would comply with the ethical requirements and satisfy stakeholders’ interests. The results also show that the effect of CSR on earnings management is particularly stronger in more independent boards and with high institutional ownership structure. These corporate governance devices help mitigating managerial opportunistic behavior.